Heatstroke-induced acute kidney injury and the innate immune system - Goto, Hiroyasu; Kinoshita, Manabu; Oshima, Naoki (Frontiers in Medicine, 2023)
Heatstroke can cause multiple organ failure and systemic inflammatory response syndrome as the body temperature rises beyond the body's ability to regulate temperature in a hot environment. Previous studies have indicated that heatstroke-induced acute kidney injury (AKI) can lead to chronic kidney disease. Therefore, there is an urgent need to elucidate the mechanism of heatstroke-induced AKI and to establish methods for its prevention and treatment. Recent reports have revealed that innate immunity, including neutrophils, macrophages, lymphocytes, and mast cells, is deeply involved in heat-induced AKI. In this review, we will discuss the roles of each immune cell in heat-induced renal injury and their potential therapeutic use.